Masculinidades em cena: o modo de ser e de pensar o metrossexual a partir das telenovelas - OLIVEIRA JÚNIOR, Edyr Batista de (Universidade Federal do Pará, 2013)
I tried to analyze the perceptions of subjects about the way of being and thinking the metrosexual character from Brazilian soap operas. The use of characters from this kind of program for research was important because soap operas are productions that contribute to the viewing of behaviors and dissemination of the "new", besides having great input in Brazilian homes. Because of this, I conducted sixteen interviews with five women and eleven men, all residing in Belém, Pará, undergraduate or graduated in order to show how these people see the male characters that are presented on electronic serials and if they perceive metrosexual characters or with metrosexual characteristics in Brazilian soap operas. I also investigated what some operators of communication - writers, authors, actors and academic writers who study Brazilian soap operas – think about the relation of the male audience with this type of program, through interviews they gave to some media and / or academic papers they wrote. Moreover, I discussed the construction of the metrosexual and the current association of this male type with homosexuality. Thus, I approached the comprehension of my interlocutors on three characters which I focused in my interviews: Narciso (Vladimir Brichta), from Belíssima (2005), Thomas (Leonardo Miggiorin) from Cobras e Lagartos (2006) and Carlos (Carlos Casagrande), from Viver a Vida (2009), verifying the characteristics that make men represented in these roles recognized or not as vain. It will be possible to see that the idea of a male type unconcerned about what he wears, who uses soap to wash his hair not to spend much time with shampoos and conditioners, for example, has lost ground in the contemporary scene, once men, more and more, externalize their vanity, contributing to the "manufacture" of beautiful and desired bodies.